Integrative cognitive remediation for early psychosis: Results from a randomized controlled trial. (March 2019) - Vidarsdottir, Olina G.; Roberts, David L.; Twamley, Elizabeth W.; Gudmundsdottir, Berglind; Sigurdsson, Engilbert; Magnusdottir, Brynja B.
Highlights: Three widely used cognitive remediation approaches were integrated. Integrated cognitive remediation (ICR) is a 12-week group-based intervention. Multiple domains of neurocognition and social cognition improved. ICR is a time-effective, feasible intervention for early psychosis. Abstract: Early application of cognitive remediation may help prevent the development of long-term functional impairments that characterize psychotic disorders. Interventions that encompass both neurocognitive and social-cognitive training may work synergistically to bridge the gap between cognitive gains and functional outcomes in early psychosis. We integrated three cognitive remediation approaches: Neuropsychological Educational Approach to Remediation (NEAR), Compensatory Cognitive Training (CCT), and Social Cognition and Interaction Training (SCIT), and evaluated the effects on cognition, clinical symptoms, self-assessed and informant-assessed social functioning in early psychosis. A total of 49 patients diagnosed with primary psychotic disorder seeking service at an early-intervention service in Iceland were randomized to either a waiting-list control group ( n = 24) or a 12-week group-based integrative cognitive remediation ( n = 25). Neurocognition, social cognition, community functioning and clinical symptoms were assessed at baseline and post-treatment. The intervention group showed significant improvements in verbal memory, cognitive flexibility, working memory, ToM and a significant reduction in hostile attributions, compared to those receiving standard treatment alone, but there were no differences between groups on measures of social functioning or clinical symptoms. The intervention was well tolerated and received high treatment satisfaction ratings. Findings indicate that integrated cognitive remediation has potential to improve neurocognition and social cognition in early psychosis.